2005
DOI: 10.1111/j.0105-1873.2005.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch testing with a new fragrance mix – reactivity to the individual constituents and chemical detection in relevant cosmetic products

Abstract: 50 patients (2.9%) showed a positive reaction to 14% FM II and 70 patients (4.1%) to 28% FM II. 24/50 (48%) produced a positive reaction to 1 or more of the individual constituents of 14% FM II and 38/70 (54.3%) to 28% FM II, respectively. If doubtful reactions to individual constituents are included, the break-down testing was positive in 74% and 70%, respectively. Patients with a positive reaction to 14% FM II showed a higher rate of reactions to the individual constituent of the 28% FM II: 36/50 (72%). Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
7
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 33 publications
8
79
7
1
Order By: Relevance
“…In fact, to our knowledge, no previous studies have investigated the prevalence of fragrance mix 2 sensitization in the general population. The frequency of contact sensitization to fragrances strictly depends on the number of allergens tested, and patch testing with fragrance mix 2 detects additional patients sensitive to perfumes and missed by fragrance mix 1 testing [7,12,13]; thus, we would expect that the overall prevalence of contact sensitization to fragrances would be higher than prevalence estimates so far. This inclusion could account, at least in part, for the relatively high frequency of contact sensitization to fragrances we found in the pilot investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, to our knowledge, no previous studies have investigated the prevalence of fragrance mix 2 sensitization in the general population. The frequency of contact sensitization to fragrances strictly depends on the number of allergens tested, and patch testing with fragrance mix 2 detects additional patients sensitive to perfumes and missed by fragrance mix 1 testing [7,12,13]; thus, we would expect that the overall prevalence of contact sensitization to fragrances would be higher than prevalence estimates so far. This inclusion could account, at least in part, for the relatively high frequency of contact sensitization to fragrances we found in the pilot investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Further difficulties in establishing estimates of contact sensitizations to fragrances are related to the variability in the concentrations of allergens in solution (or petrolatum) [12,18]. Moreover, one controversial issue is the reliability of reactions to a fragrance mix [18,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies are by their nature incapable of unambiguously designating citronellol as the cause of the patient's condition. While its inclusion in cosmetic labeling declarations [36] and routine patch testing materials such as 'FM II' [23] may provide further information on its possible causal role in allergic contact dermatitis, the evidence currently available does not indicate that citronellol is a major fragrance allergen. Prospective clinical correlation patch test studies should provide clearer data as to the certainty of this interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent to the review period, a publication has reported studies on a new 'Fragrance Mix II' (FM II) [23] . In this study, 1,701 patients were patch tested to this new mixture, and subsequent patch testing of positively reacting patients to the individual components produced 2 positive (+) and 18 irritant or doubtful (?/IR) reactions to 0.5% citronellol.…”
Section: Tests Producing Reactionsmentioning
confidence: 99%
See 1 more Smart Citation